The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpls.2022.1001206
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, characterization, and expression analysis of UDP-glycosyltransferase genes associated with secondary metabolism in alfalfa (Medicago sativa L.)

Abstract: Uridine diphosphate glycosyltransferases (UGTs) are enzymes that catalyze glycosylation modifications and play an essential role in regulating plant metabolism. Alfalfa (Medicago sativa L.) is the most important legume in the world due to its high yields and protein content; however, the UGT genes in alfalfa have not yet been studied. Identifying UGT genes with metabolic roles in alfalfa is essential for identifying and modifying genetic traits that are relevant to yield and quality. In this study, 90 of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…With the development of high-throughput sequencing technology, plant transcriptomes are being studied more and more extensively, facilitating the mining of biosynthetic pathways of many high-value plant natural products. , Currently, transcriptome sequencing technology combined with bioinformatics analysis is an effective means to mine UGTs. de Costa et al and Kim et al identified glycosyltransferases Ca UGT73AD1 and Ca UGT73AH1 mediating glycosylation of asiatic acid from the C. asiatica transcriptome, but the UGTs that ultimately generate asiaticoside and madecassoside need to be further investigated. , Asiaticoside and madecassoside share the same sugar chain (glucose–glucose–rhamnose) linking their carboxyl groups .…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput sequencing technology, plant transcriptomes are being studied more and more extensively, facilitating the mining of biosynthetic pathways of many high-value plant natural products. , Currently, transcriptome sequencing technology combined with bioinformatics analysis is an effective means to mine UGTs. de Costa et al and Kim et al identified glycosyltransferases Ca UGT73AD1 and Ca UGT73AH1 mediating glycosylation of asiatic acid from the C. asiatica transcriptome, but the UGTs that ultimately generate asiaticoside and madecassoside need to be further investigated. , Asiaticoside and madecassoside share the same sugar chain (glucose–glucose–rhamnose) linking their carboxyl groups .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in grapevines, UGT 85 A 24 and UGT 85 A 25 are expressed in berries and influence their flavor, whereas UGT 85 A 26 and UGT 85 A 27 are predominantly expressed in leaves and enhance plant defense against herbivores and pathogens . In Medicago sativa, UGT 28, UGT 54, and UGT 79 are highly expressed in leaves, potentially due to the increased accumulation of flavonoids and terpenoids . Our previous study revealed that CsUGT 75 L 12 and CsUGT 79 B 28 are expressed in the tender tissues of tea plants, and the enzymes encoded by these genes catalyze the biosynthesis of bitter flavonoid 7- O -neohesperidosides .…”
Section: Discussionmentioning
confidence: 99%
“…33 In Medicago sativa, UGT28, UGT54, and UGT79 are highly expressed in leaves, potentially due to the increased accumulation of flavonoids and terpenoids. 34 Our previous study revealed that CsUGT75L12 and CsUGT79B28 are expressed in the tender tissues of tea plants, and the enzymes encoded by these genes catalyze the biosynthesis of bitter flavonoid 7-O-neohesperidosides. 24 The relative expression analysis conducted in this study revealed that 32.14% of all CsUGT genes were expressed in the tender shoots of C. sinensis (Figure 3a), whereas 35% were expressed in C. sinensis var.…”
Section: Phylogenetic Analysis Revealed the Functional Differentiatio...mentioning
confidence: 99%
“…The UGT genes of four Rubus species were unevenly distributed among groups, and there were great differences among species. The groups L and O had the most members in R. chingii (31 and 32), and group L also occupied most members in R. idaeus (26) and R. occidentalis (17), respectively, and group E in R. corchorifolius (24) had the most members. Furthermore, compared with the other three Rubus plants UGTs, the RchUGTs and RchUGTs lacked group G and N, respectively.…”
Section: Phylogenetic Analysis Of Ugt Family Genesmentioning
confidence: 99%
“…The UGTs of plants not only participate in the synthesis of plant secondary metabolites, but also have a variety of biological functions, such as a role in plant antitoxin and defense mechanisms, the response to abiotic stress, and in the regulation of plant hormones [13,16,17]. UGT genes have been identified in many plants, including Arabidopsis thaliana (121) [9], Populus trichocarpa (191) [18], wheat (179) [19], Gossypium raimondii (142) [20], Quercus robur (244) [21], apple (299) [22], Morella rubra (152) [23], alfalfa (90) [24], and so on. Up to now, there have been few studies on the UGT family of R. chingii, only mentioned in the publication of the Chinese raspberry genome [2], and the number of identified UGT genes may be incomplete.…”
Section: Introductionmentioning
confidence: 99%